2007
DOI: 10.1128/jvi.01292-06
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Alpha Interferon Signaling by Hepatitis B Virus

Abstract: Alpha interferon (IFN-␣) and pegylated IFN-␣ (pegIFN-␣) are used for the treatment of chronic hepatitis B (CHB). Unfortunately, only a minority of patients can be cured. The mechanisms responsible for hepatitis B virus (HBV) resistance to pegIFN-␣ treatment are not known. pegIFN-␣ is also used to treat patients with chronic hepatitis C (CHC). As with chronic hepatitis B, many patients with chronic hepatitis C cannot be cured. In CHC, IFN-␣ signaling has been found to be inhibited by an upregulation of protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 32 publications
5
90
3
Order By: Relevance
“…In agreement with our data, a recent study has shown that IFNβ promoter activation induced by SeV was attenuated in HepG2.2.15 cells (Wang and Ryu, 2010). Replication of HBV does not have an effect on phosphorylation of STAT1 in cells stimulated with IFN (Christen et al, 2007), and we confirmed this result. However, we also found that signaling events downstream of STAT1 was not affected by HBV (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In agreement with our data, a recent study has shown that IFNβ promoter activation induced by SeV was attenuated in HepG2.2.15 cells (Wang and Ryu, 2010). Replication of HBV does not have an effect on phosphorylation of STAT1 in cells stimulated with IFN (Christen et al, 2007), and we confirmed this result. However, we also found that signaling events downstream of STAT1 was not affected by HBV (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…However, we also found that signaling events downstream of STAT1 was not affected by HBV (Fig. 5F), which are contradictive to published studies that show nuclear translocation and DNA binding ability of STAT1 are impaired by HBV polymerase (Wu et al, 2007) and surface proteins and/or HBx (Christen et al, 2007) in Huh7 cells, respectively. Cell type specific differences might explain the apparent discrepancy.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Inhibition of the key IFN-a signal transducer Stat1 by HBV has been suggested to antagonize the IFN response (35,36). In this study, we found that miR-146a, which targets Stat1, is significantly upregulated in the T cells of patients with CHB, which could shed light on the mechanism of the limited effectiveness of therapeutic IFN-a in CHB.…”
Section: Discussionmentioning
confidence: 55%